Language exposure and subject familiarity as correlates of senior secondary school students’ achievement in narrative writing - Oladotun Opeoluwa Olagbaju,; Nurudeen Oluwaseun Jimoh, (Technium Social Sciences Journal, 2020)
Narrative writing is often an option in English composition examination, especially in WAEC/NECO conducted English language Paper 1. Performance in essay writing has been found to determine the overall success in English language. Efforts to improve students’ performance in the subject have largely focused on instructional strategies without much attention to process-based variables such as language exposure and subject familiarity that can influence learning outcomes in ESL classrooms. Despite the contributions of these studies to pedagogical practices in ESL classroom, students’ achievement in English composition has not improved significantly. However, process-related variables such as quality and volume of exposure to the target language and subject familiarity have been found to predict learning outcomes in a second/foreign language classroom. Therefore, this study examined the relationship between language exposure and subject familiarity on achievement in narrative essay. The study tested three null hypotheses and a total of 350 participants were randomly selected from four senior secondary schools in Ibadan North Local Government Area, Nigeria. Data was collected using two research instruments and the results showed a positive non-significant relationship between the independent variables and students’ achievement in narrative essay. Also, there were no composite and relative contributions of language exposure and subject familiarity to students’ achievement in expository essay.